(untitled) (Discourse of Law and Administration, 2021)
Currently, in the law, apart from traditional forms of legal transactions, there are documentary and electronic forms. They are also used in labor law. The purpose of this article is to indicate the possibilities and legitimacy of using the documentary and electronic form in the employment relationship and the use of electronic form to store employee documentation. In employment relationships, the documentary form is mainly used for the information obligation. In this form, the employment contract may also be terminated by mutual agreement of the parties. On the other hand, the electronic form, due to the requirement to have a secure electronic signature with a qualified certificate, is a significant obstacle for many employees.